A Study on People#x2019;s Perception towards Health Insurance amid COVID-19 Outbreak: A Perspective from Bangladesh (Global Journal of Management and Business Research, 2021)
The Health Sector of Bangladesh is been in a very fragile condition since its independence. The situation is deteriorating day by day, although a great effort has been provided by Government, national and international organizations. Every year the allocation for health and family welfare ministry in the national budget is bouncing, yet it is the lowest in terms of GDP in South Asia. Moreover, the Government-sponsored hospitals couldn't provide quality treatment due to their resource, workforce, and capacity constraints.
Keywords: insurance; health insurance; covid-19; health consciousness; inclusiveness